Method for forming the streamlined surface of suspension insulators - Baidabekov, Ауез; Dzhumabaev A.A., Джумабаев А.А.; Kusebaev, Уалихан (Рroblems of engineering and professional education, 2023)
The article deals with the problems of extending the working time of insulators used in overhead power lines and increasing the level of reliable service.